The ASEAN Economic Community and new regionalism : A Neorealist Analysis - Jones, William J. (2015)
The ASEAN Charter proposed by the Eminent Persons Group in 2006 and drafted by the High-Level Task Force is seen as a progressive step forward in the deepening and evolution of ASEAN regional integration. With its signing and ratification, ASEAN will attempt to transform its character to be a regional institution in form and function both within the region and internationally. The purpose of this paper is to assess the development of the ASEAN Economic Community (“AEC”) to see if it intends to build a community or is a neorealist extension of traditional practice by ASEAN’s member states by assessing the AEC from a “new regionalism” perspective. It is the view of this writer that the ASEAN Economic Community as currently structured is used to keep and/or increase national order and interests in the face of destabilizing forces of globalization. This critique will assess the ASEAN Economic Pillar as a component of New Regionalism from a heoretical neorealist perspective,thereby attempting to identify components which have contributed to an economic community forming in ASEAN in the post-Cold War period and to possibly identify some critical factors indicating where ASEAN regionalism will lead.